ChemInform Abstract: Efficient Multi‐Component Synthesis of 1, 4‐Benzodiazepine‐3, 5‐diones: A Petasis‐Based Approach. Issue 50 (December 2015) - Noushini, Saeedeh; Mahdavi, Mohammad; Firoozpour, Loghman; Moghimi, Setareh; Shafiee, Abbas; Foroumadi, Alireza
Abstract: The one‐pot reaction between anthranilic acid amides (I), glyoxalic acid (II) and arylboronic acids (III) gives the title compounds in good yields.